How to organise teaching activities for the scoring of cardiorespiratory polygraphies? Experiences from three Swedish Sleep Society teaching courses. (23rd September 2018) - Grote, Ludger
Abstract: Education in the scoring of sleep‐disordered breathing is organised differently and data on the evaluation of teaching strategies based on student ratings are sparse. The aim of the study was to analyse the gain in theoretical and practical knowledge achieved during different course settings offered by a national sleep society. The course contained 1 hr of theoretical teaching (scoring rules and recording methodology) and 2.5 hr of practical scoring (physiological breathing, obstructive/central sleep apnea and hypoventilation). Three different settings were provided: a large scoring group including participants with mixed experiences (1), a small scoring group with inexperienced scorers (2), and guided scoring for experienced scorers (3). Evaluation was performed at the end of the course. Data from 67 out of 82 participants (79%) were analysed (42 nurses/technicians and 25 physicians/dentists). Previous scoring experience was limited, moderate and extended in 25, 26, and 15 students, respectively. Gain of practical knowledge and overall course rating were significantly higher in settings 2 and 3 compared with 1 ( p = 0.005 and p = 0.018 respectively). Guided scoring was the preferred practical teaching setting in experienced scorers, whereas scoring in large groups together with an experienced student was preferred in newcomers. Profession did not influence gain of knowledge, course satisfaction or preferred course design. From the student's perspective, consensus scoring in groups or guided scoring for all students may have advantages compared with single/small‐group scoring settings. Technical teaching knowledge of faculty members is of significant importance.